2003
DOI: 10.1258/jrsm.96.3.118
|View full text |Cite
|
Sign up to set email alerts
|

Five steps to conducting a systematic review

Abstract: Systematic reviews and meta-analyses are a key element of evidence-based healthcare, yet they remain in some ways mysterious. Why did the authors select certain studies and reject others? What did they do to pool results? How did a bunch of insignificant findings suddenly become significant? This paper, along with a book 1 that goes into more detail, demystifies these and other related intrigues. A review earns the adjective systematic if it is based on a clearly formulated question, identifies relevant studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
306
0
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 624 publications
(325 citation statements)
references
References 1 publication
0
306
0
19
Order By: Relevance
“…The adjective "systematic" implies conducting the review based on a clearly formulated question, identifying relevant studies, appraising their quality, and summarizing the evidence using explicit methodologies. The term "systematic review" implies obeying the predefined rules [42] .…”
Section: Discussionmentioning
confidence: 99%
“…The adjective "systematic" implies conducting the review based on a clearly formulated question, identifying relevant studies, appraising their quality, and summarizing the evidence using explicit methodologies. The term "systematic review" implies obeying the predefined rules [42] .…”
Section: Discussionmentioning
confidence: 99%
“…12, No. 6;2017 was conducted following the PRISMA guidelines and according to the recommendations of Khan, Kunz, Kleijnen, and Antes (2003). Using keywords, the research was conducted on PubMed, Scopus, and ISI Web of Knowledge research engines, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As the number of studies in this area was found to be very low, it was necessary to create a process to conduct this review that included qualitative, quantitative and mixed-method studies. The method devised for this review was primarily informed by Khan's et al's five step reviewing process, which involves framing focus questions, identifying relevant work, "assessing the quality of studies", "summarizing the evidence", and "interpreting the findings" [35].…”
Section: Reviewmentioning
confidence: 99%